2021
DOI: 10.1590/1807-3107bor-2021.vol35.0136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational strategy combined with ART on oral health-related quality of life: a controlled clinical trial

Abstract: This study aimed to assess whether complementing atraumatic restorative treatment (ART) with oral health educational strategies (OHES) improves the perception of oral health-related quality of life (OHRQoL) and clinical oral outcomes. A controlled clinical trial included 93 six-to eight-year-old students from five public schools of Piracicaba, Saltinho, and Charqueada municipalities (State of São Paulo, Brazil) divided into 3 groups (31 children each) which received: OHES (caries-free), ART (dental caries), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…Thus, in this study, the OHES may have increased the children's sense of coherence [34], favoring a more accurate perception of their oral problems and symptoms, as observed by Sousa et al [18].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Thus, in this study, the OHES may have increased the children's sense of coherence [34], favoring a more accurate perception of their oral problems and symptoms, as observed by Sousa et al [18].…”
Section: Discussionsupporting
confidence: 62%
“…Although some studies have already demonstrated the effect of conventional dental caries treatment on improving OHRQoL in children [15,16], there is little evidence of the influence of ART on OHRQoL in the child population [7,9,17]. In Sousa et al [18] study, including health educational strategies in the ART treatment plan was a determinant for the child's perception of improved oral health after restorative treatment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation